Decision Making Empowerment Among Women With And Without Microcredit Coverage - Ferdousi, Nigar; Islam, Md Ziaul; Sultana, Sadia; Jahan, Nur Wa Bushra (Journal of Preventive and Social Medicine, 2022)
Background: Women of Bangladesh, especially rural women experience adverse situations in terms of socioeconomic inequality and gender disparity. This study compared the decision making empowerment among women with and with microcredit coverage. Methods: The study design was a cross sectional study in two sample situation. Total 258 women, 129 with microcredit coverage and 129 without microcredit, was selected by convenience sampling technique from Pakdy and Thantoly of Madaripur district in Bangladesh. Data were collected by face to face interview with the help of a semistructured questionnaire. Data were analyzed by SPSS software. Quality control and ethical issues were maintained strictly. Results: The study revealed that mean (±SD) age of women with microcredit coverage was 30.27(±9.62) years and women without microcredit coverage was 30.78(±8.98) years. Mean (±SD) score of decision making empowerment was significantly higher among women with microcredit (34.02±3.92) than without microcredit (17.89±5.20) (p<0.01). Mean (±SD) score of household related decision making empowerment among women with microcredit 14.22 (±1.96) was significantly higher (p<0.01). Mean (±SD) score of physical movement related decision making empowerment among women with microcredit (9.39±1.57) was significantly higher (p<0.01). Mean (±SD) score of economic decision making empowerment was significantly higher among women with microcredit coverage (10.50±1.324) (p<0.01). There were significant positive relationships between age of women with microcredit coverage and decision making empowerment (r=0.133). There were significant positive relationships between age (r=0.375) and monthly family income (r=0.308) of women without microcredit coverage and decision making empowerment. Conclusion: This study revealed that rural women had enhanced their decision making empowerment by participating in microcredit programmes. JOPSOM 2021; 40(2):1-8